2021
DOI: 10.1590/0047-2085000000311
|View full text |Cite
|
Sign up to set email alerts
|

Patient subjective experience of treatment with long-acting injectable antipsychotics: a systematic review of qualitative studies

Abstract: Objective: To gain a better understanding of how long-acting injectable antipsychotic (LAI) therapy is perceived by patients. Methods: A search for qualitative studies has been carried out on PubMed, Google Scholar, PsycINFO and PsycArticles, yielding 11 studies suitable for a review of qualitative studies. The reporting approach chosen was meta-ethnography, following the ENTREQ statement recommendations. Key concepts common to the different studies were extrapolated and then analysed in a systematic and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Poor treatment adherence and compliance with oral antipsychotics (OAPs) reportedly lead to high relapse rates, which translates into poor clinical outcomes and a high economic burden (18). A qualitative study's systematic review on the experience of patients with LAIs showed that patients' education is essential, as well as a close therapeutic context with the attending physician, to increase patient adherence to such therapeutics (19). In the cases where this happens, the overall subjective experience of patients is deemed as very positive (9)(10)(11)18).…”
Section: Introductionmentioning
confidence: 99%
“…Poor treatment adherence and compliance with oral antipsychotics (OAPs) reportedly lead to high relapse rates, which translates into poor clinical outcomes and a high economic burden (18). A qualitative study's systematic review on the experience of patients with LAIs showed that patients' education is essential, as well as a close therapeutic context with the attending physician, to increase patient adherence to such therapeutics (19). In the cases where this happens, the overall subjective experience of patients is deemed as very positive (9)(10)(11)18).…”
Section: Introductionmentioning
confidence: 99%